Interaction between HFE and haptoglobin polymorphisms and its relation with plasma glutathione levels in obese children - Aguiar, Laura; Marinho, Cláudia; Martins, Rute; Alho, Irina; Ferreira, Joana; Levy, Pilar; Faustino, Paula; Bicho, Manuel; Inacio, Angela (Cellular and Molecular Biology, 2019)
Obesity among children has emerged as a serious public health problem. The growing prevalence of childhood obesity has led to the appearance of serious complications, including a chronic systemic inflammation associated with oxidative stress. In the present study, we analysed the interaction between two genes related with iron metabolism - HFE and haptoglobin – and the plasmatic concentration of glutathione, as a way to evaluate the antioxidant response capacity in obesity. To achieve this, 118 obese children and 89 eutrophic children were recruited for the study. Results showed that although obese children present a significantly decreased tGSH levels, once we analysed separately children based on their haptoglobin phenotype, the decreased tGSH levels is significant only for the Hp 2 allele. Additionally, Hp 2.2 obese children carrying H63D polymorphism show significantly lower tGSH/GSSG values. Our results found an association of haptoglobin and HFE with oxidative stress in childhood obesity.